Hepatic hemangioendothelioma in a two-year-old boy - Benedetti, Juan Luis; Gutiérrez, Maria Del Carmen; Chavarría, Oscar (Cirugía del Uruguay, 1986)
We report a case of Infantil Hepatic Hemangioendothelioma in a 2 years old girl. She was admitted because of abdominal mass. Treatment consisted of resection of the tumor. The post operative course was uneventfull. Sorne anatomic and clinical aspects of the disease are reviewed.